Origin and evolution of Native American mtDNA variation: a reappraisal - FORSTER P; HARDING R; BANDELT H. J.; TORRONI, ANTONIO (1996)
The timing and number of prehistoric migrations involved in the settlement of the American continent is subject to intense debate. Here, we reanalyze Native American control region mtDNA data and demonstrate that only an appropriate phylogenetic analysis accompanied by an appreciation of demographic factors allows us to discern different migrations and to estimate their ages. Reappraising 574 mtDNA control region sequences from aboriginal Siberians and Native Americans, we confirm in agreement with linguistic, archaeological and climatic evidence that (i) the major wave of migration brought one population, ancestral to the Amerinds, from northeastern Siberia to America 20,000-25,000 years ago and (ii) a rapid expansion of a Beringian source population took place at the end of the Younger Dryas glacial phase approximately 11,300 years ago, ancestral to present Eskimo and Na-Dene populations.